Flame-retardant high-strength fiberboard and method for producing the same
By combining modified wood fibers and flame retardants, an amorphous titanium dioxide coating layer and a P–O–Si covalent network are formed, which solves the contradiction between the flame retardancy and mechanical properties of fiberboard and realizes high-strength, weather-resistant and hydrophobic fiberboard.
Patent Information
- Application Number
- CN202511604161.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-05
- Publication Date
- 2026-02-03
- Estimated Expiration
- 2045-11-05
AI Technical Summary
Existing technologies struggle to achieve effective flame retardancy without compromising the mechanical properties of fiberboard, thus limiting its practical applications.
A combination of modified wood fibers and flame retardants is used to form an amorphous titanium dioxide coating layer and a P–O–Si covalent network on the surface of wood fibers by modifying the surface with isopropoxy titanium, dimethyl aminomethylphosphonate, and trimethoxy(3,3,3-trifluoropropyl)silane. Diatomaceous earth is modified with propyltriethoxysilane to improve compatibility and dispersibility.
It achieves excellent mechanical properties, flame retardancy, weather resistance and hydrophobicity of fiberboard, solves the problem of decreased mechanical properties caused by the addition of flame retardants, and improves the overall performance of fiberboard.
Smart Images

Figure CN121061992B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of fiberboard, and particularly relates to a flame-retardant high-strength fiberboard and a preparation method thereof. BACKGROUND
[0002] The fiberboard is a man-made board material made of wood fiber or other plant fiber as raw material and interwoven into a shape. It has the advantages of uniform material, small strength difference in longitudinal and transverse directions, and less cracking. Compared with the original wood board, the fiberboard can significantly reduce wood consumption and improve the comprehensive utilization efficiency of wood resources. Therefore, the fiberboard is increasingly replacing the original wood board and is widely used in real estate, transportation, building materials, interior decoration and packaging fields.
[0003] For different application fields and use scenarios, specific performance requirements are usually proposed for the fiberboard. In order to meet these differentiated needs, it is of great significance to develop various functional fiberboards. At present, one of the common functional methods is to add a flame retardant to the fiberboard to prepare a flame-retardant fiberboard. However, the introduction of the flame retardant often affects the combination between the adhesive and the fiber raw material, thereby weakening the mechanical properties of the fiberboard. If the amount of the flame retardant is reduced, it is difficult to achieve the desired flame-retardant effect; and if the amount is increased, it will significantly damage the mechanical properties. Therefore, under the existing technical conditions, the mechanical properties and the flame-retardant properties of the fiberboard are often difficult to be considered, and this contradiction greatly limits the wide application of the fiberboard in practice. Based on this, it is urgent to provide a fiberboard with excellent mechanical properties and flame-retardant properties to meet market demand. SUMMARY
[0004] In order to overcome the shortcomings of the prior art, the first purpose of the present application is to provide a flame-retardant high-strength fiberboard with excellent mechanical properties and flame-retardant properties.
[0005] The second purpose of the present application is to provide a preparation method of the flame-retardant high-strength fiberboard, which is simple in process.
[0006] In order to achieve the above-mentioned purposes, the technical scheme adopted by the present application is as follows:
[0007] A flame-retardant high-strength fiberboard, comprising the following components in parts by weight: modified wood fiber 90-100 parts, flame retardant 15-20 parts, and adhesive 7-16 parts.
[0008] The preparation process of the modified wood fiber is as follows:
[0009] (1) Wood fiber is added to anhydrous ethanol, and then isopropoxy titanium and trimethyl octadecyl ammonium chloride are added for heating reaction. After the reaction is completed, the pretreated wood fiber is obtained by filtering, washing and drying.
[0010] (2) the pretreated wood fiber is added into deionized water, dimethyl methylphosphonate, trimethoxy (3,3,3-trifluoropropyl) silane and aluminum chloride are added for reaction, and after the reaction is completed, centrifugation and drying are performed to obtain the modified wood fiber.
[0011] Further, the wood fiber, titanium isopropoxide and trimethyl octadecyl ammonium chloride in step (1) are used in a ratio of 1g: (30-60)mL: (20-50)g.
[0012] Further, the wood fiber has a length of 2-4mm.
[0013] Further, the heating reaction in step (1) is performed at a temperature of 40-50℃ for 8-10h.
[0014] Further, the wood fiber, dimethyl methylphosphonate, trimethoxy (3,3,3-trifluoropropyl) silane and aluminum chloride in step (2) are used in a mass ratio of 1: (0.1-0.3): (2-5): (2-4); and the reaction is performed for 2-5h.
[0015] Further, the preparation process of the flame retardant is as follows: diatomite is added into N,N-dimethylformamide, propyl triethoxysilane isocyanate is added, and reaction is performed at 50-60℃ for 1-3h; after the reaction is completed, filtration, washing and drying are performed to obtain the flame retardant.
[0016] Further, the diatomite and propyl triethoxysilane isocyanate are used in a mass ratio of 1: (0.05-0.15).
[0017] Further, the adhesive is an isocyanate adhesive.
[0018] Further, the isocyanate adhesive is a polymethylene polyphenyl polyisocyanate adhesive.
[0019] Further, the adhesive further contains paraffin wax, and the mass fraction of the paraffin wax in the adhesive is 0.5-2%.
[0020] The preparation method of the above flame-retardant high-strength fiberboard comprises the following steps:
[0021] According to the weight part ratio, each raw material is weighed, the modified wood fiber and the flame retardant are uniformly mixed, the adhesive is added, stirring is performed, and then the mixture is transferred into a mold, and pouring, rolling, cooling are performed to obtain the flame-retardant high-strength fiberboard.
[0022] Further, the rolling is performed at a temperature of 160-180℃ and a pressure of 2-3MPa.
[0023] The beneficial technical effects of the present application are that:
[0024] 1. The present application provides a flame-retardant high-strength fiberboard with excellent mechanical properties, flame-retardant properties, weather resistance and hydrophobicity.
[0025] 2. The flame-retardant high-strength fiberboard of the present application uses modified wood fibers, which significantly improves the hydrophobicity, weather resistance, mechanical properties and flame retardancy of the fiberboard. Specifically, the modification process of the modified wood fibers is realized in two steps: first, isopropoxy titanium forms an amorphous titanium dioxide coating layer on the surface of the wood fibers, which not only improves the weather resistance of the material, but also endows it with the ability to photocatalytically degrade formaldehyde; second, dimethylammonium methylphosphonate and trimethoxy (3,3,3-trifluoropropyl) silane undergo hydrolysis and condensation on the titanium dioxide layer to form a stable P–O–Si covalent network. This structure simultaneously introduces phosphorus-based flame-retardant elements and long fluorocarbon chains, which not only endow the wood fibers with intrinsic hydrophobicity, but also produce a synergistic flame-retardant effect with subsequent flame retardants. This modified layer effectively consolidates the fiber structure, solving the industry problem of mechanical property degradation caused by the addition of conventional flame retardants.
[0026] 3. The flame-retardant high-strength fiberboard of the present application also adds a flame retardant to improve the flame retardancy of the fiberboard. Specifically, isocyanate propyl triethoxy silane is used to graft modify the surface of diatomite, improving the compatibility and dispersibility of the flame retardant in the wood fiber matrix and fundamentally solving the problem of easy agglomeration of diatomite. BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 SEM image of the modified wood fibers obtained in Preparation Example 1. DETAILED DESCRIPTION
[0028] The following further describes the present application in conjunction with specific preferred embodiments, which cannot be deemed to limit the specific implementation of the present application to these descriptions. For those of ordinary skill in the art to which the present application belongs, without departing from the concept of the present application, a number of simple deductions or substitutions can also be made, which should all be considered within the protection scope of the present application. The specific conditions not mentioned in the examples are carried out according to the conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if not specifically mentioned, are conventional products obtained through market channels.
[0029] The length of the wood fibers in the preparation example of the present application is 2-4 mm. The adhesive in the examples of the present application is a multi-methylene multi-phenyl multi-isocyanate adhesive, which also contains 1% of paraffin wax.
[0030] Preparation Example 1
[0031] This preparation example provides a modified wood fiber, and the preparation method is as follows:
[0032] (1) according to the amount ratio of lignocellulose, titanium isopropoxide, trimethyl octadecyl ammonium chloride, anhydrous ethanol 1g: 50ml: 40g: 150ml, lignocellulose is added to anhydrous ethanol, then titanium isopropoxide and trimethyl octadecyl ammonium chloride are added, and the reaction is carried out at 45℃ for 9h. After the reaction is completed, filtration, washing and drying are carried out to obtain pretreated lignocellulose;
[0033] (2) according to the mass ratio of pretreated lignocellulose, dimethyl aminomethyl phosphonate, trimethoxy (3, 3, 3-trifluoropropyl) silane, aluminum chloride 1: 0.2: 4: 3, the pretreated lignocellulose is added to deionized water, then dimethyl aminomethyl phosphonate, trimethoxy (3, 3, 3-trifluoropropyl) silane and aluminum chloride are added, and the reaction is carried out at room temperature for 3h. After the reaction is completed, centrifugation and drying are carried out to obtain the modified lignocellulose. The SEM diagram of the modified lignocellulose is shown in Figure 1 .
[0034] Preparation Example 2
[0035] The present preparation example provides a modified lignocellulose, and the preparation method is as follows:
[0036] (1) according to the amount ratio of lignocellulose, titanium isopropoxide, trimethyl octadecyl ammonium chloride, anhydrous ethanol 1g: 30ml: 20g: 150ml, lignocellulose is added to anhydrous ethanol, then titanium isopropoxide and trimethyl octadecyl ammonium chloride are added, and the reaction is carried out at 40℃ for 10h. After the reaction is completed, filtration, washing and drying are carried out to obtain pretreated lignocellulose;
[0037] (2) according to the mass ratio of pretreated lignocellulose, dimethyl aminomethyl phosphonate, trimethoxy (3, 3, 3-trifluoropropyl) silane, aluminum chloride 1: 0.1: 2: 2, the pretreated lignocellulose is added to deionized water, then dimethyl aminomethyl phosphonate, trimethoxy (3, 3, 3-trifluoropropyl) silane and aluminum chloride are added, and the reaction is carried out at room temperature for 2h. After the reaction is completed, centrifugation and drying are carried out to obtain the modified lignocellulose.
[0038] Preparation Example 3
[0039] The present preparation example provides a modified lignocellulose, and the preparation method is as follows:
[0040] (1) according to the amount ratio of lignocellulose, titanium isopropoxide, trimethyl octadecyl ammonium chloride, anhydrous ethanol 1g: 60ml: 50g: 150ml, lignocellulose is added to anhydrous ethanol, then titanium isopropoxide and trimethyl octadecyl ammonium chloride are added, and the reaction is carried out at 50℃ for 8h. After the reaction is completed, filtration, washing and drying are carried out to obtain pretreated lignocellulose;
[0041] (2) The pretreated wood fiber, dimethyl amino methyl phosphonate, trimethoxy (3, 3, 3-trifluoropropyl) silane and aluminum chloride are added in the order of the pretreated wood fiber, dimethyl amino methyl phosphonate, trimethoxy (3, 3, 3-trifluoropropyl) silane and aluminum chloride in a mass ratio of 1:0.3:5:4, and the mixture is reacted at room temperature for 5 hours. After the reaction is completed, the mixture is centrifuged and dried to obtain the modified wood fiber.
[0042] Preparation Example 4
[0043] The preparation example provides a flame retardant, and the preparation method is as follows:
[0044] The diatomite, propyl triethoxysilane isocyanate and N,N-dimethyl formamide are added in the order of 1g:0.05g:20mL, and the mixture is reacted at 50°C for 3 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain the flame retardant.
[0045] Preparation Example 5
[0046] The preparation example provides a flame retardant, and the preparation method is as follows:
[0047] The diatomite, propyl triethoxysilane isocyanate and N,N-dimethyl formamide are added in the order of 1g:0.05g:20mL, and the mixture is reacted at 50°C for 3 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain the flame retardant.
[0048] Preparation Example 6
[0049] The preparation example provides a flame retardant, and the preparation method is as follows:
[0050] The diatomite, propyl triethoxysilane isocyanate and N,N-dimethyl formamide are added in the order of 1g:0.05g:20mL, and the mixture is reacted at 50°C for 3 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain the flame retardant.
[0051] Example 1
[0052] The example provides a flame-retardant high-strength fiberboard, which comprises the following components in parts by weight: 94 parts of the modified wood fiber obtained in the preparation example 1, 17 parts of the flame retardant obtained in the preparation example 4 and 9 parts of an adhesive.
[0053] The example also provides a preparation method of the flame-retardant high-strength fiberboard, which comprises the following steps:
[0054] Based on the above-mentioned parts by weight, weigh each raw material, mix the modified wood fiber obtained in Preparation Example 1 and the flame retardant obtained in Preparation Example 4 evenly, then add the adhesive, stir and transfer to a mold, pour and vibrate to form, roll press at a temperature of 170°C and a pressure of 3MPa, and after cooling, obtain the flame-retardant high-strength fiberboard.
[0055] Example 2
[0056] This embodiment provides a flame-retardant high-strength fiberboard, which, by weight, comprises the following components: 90 parts of modified wood fiber obtained in Preparation Example 2, 15 parts of flame retardant obtained in Preparation Example 5, and 7 parts of adhesive.
[0057] This embodiment also provides a method for preparing the above-mentioned flame-retardant high-strength fiberboard, including the following steps:
[0058] Based on the above-mentioned parts by weight, weigh each raw material, mix the modified wood fiber obtained in Preparation Example 2 and the flame retardant obtained in Preparation Example 5 evenly, then add the adhesive, stir and transfer to a mold, pour and vibrate to form, roll press at a temperature of 160°C and a pressure of 3MPa, and after cooling, obtain the flame-retardant high-strength fiberboard.
[0059] Example 3
[0060] This embodiment provides a flame-retardant high-strength fiberboard, which, by weight, comprises the following components: 100 parts of modified wood fiber obtained in Preparation Example 3, 20 parts of flame retardant obtained in Preparation Example 6, and 16 parts of adhesive.
[0061] This embodiment also provides a method for preparing the above-mentioned flame-retardant high-strength fiberboard, including the following steps:
[0062] Based on the above-mentioned parts by weight, weigh each raw material, mix the modified wood fiber obtained in Preparation Example 3 and the flame retardant obtained in Preparation Example 6 evenly, then add the adhesive, stir and transfer to a mold, pour and vibrate to form, roll press at a temperature of 180°C and a pressure of 2 MPa, and after cooling, obtain the flame-retardant high-strength fiberboard.
[0063] Comparative Example 1
[0064] The difference between this comparative example and Example 1 is that a mixture of wood fiber and dimethyl aminomethylphosphonate is used instead of the modified wood fiber obtained in Preparation Example 1, wherein the ratio of wood fiber to dimethyl aminomethylphosphonate is the same as in Preparation Example 1.
[0065] Comparative Example 2
[0066] The difference between this comparative example and Example 1 is that diatomaceous earth is used instead of the flame retardant obtained in Preparation Example 4.
[0067] The properties of the fiberboard obtained by the present invention will be described below.
[0068] The formaldehyde content, static bending strength, modulus of elasticity, internal bond strength, and water absorption thickness swelling rate of the fiberboards obtained in Examples 1-3 and Comparative Examples 1-2 were tested according to the methods in GB / T17657-2022. The results are shown in Table 1.
[0069] The limiting oxygen index of the fiberboards obtained in Examples 1-3 and Comparative Examples 1-2 was tested according to the method in GB / T2406.2-2009, and the results are shown in Table 1.
[0070] Table 1
[0071]
[0072] As shown in Table 1, compared with Comparative Example 1, Example 1 of the present invention significantly reduced the formaldehyde release and 24-hour water absorption thickness swelling rate of the fiberboard by adding modified wood fibers, while simultaneously improving mechanical properties. This indicates that the modified wood fibers effectively improved the hydrophobicity, weather resistance, and mechanical properties of the fiberboard. Specifically, the modification process of the wood fibers is achieved in two steps: First, isopropoxy titanium forms an amorphous titanium dioxide coating layer on the surface of the wood fibers, which not only improves the weather resistance of the material but also endows it with the ability to photocatalytically degrade formaldehyde; Second, dimethyl aminomethylphosphonate and trimethoxy(3,3,3-trifluoropropyl)silane undergo hydrolytic condensation on the titanium dioxide layer to construct a stable P–O–Si covalent network, successfully introducing long fluorocarbon chains, thereby endowing the wood fibers with inherent hydrophobic properties.
[0073] Regarding flame retardant performance, Comparative Examples 1 and 2 showed lower results than Example 1, indicating that the modified wood fiber and flame retardant used in this invention have a significant synergistic flame retardant effect. This synergistic mechanism stems from two aspects: firstly, the surface grafting of diatomaceous earth with propyltriethoxysilane effectively improves its dispersibility in the fiber matrix, overcoming the problem of diatomaceous earth's tendency to agglomerate; secondly, the P–O–Si structure formed in the modified wood fiber introduces phosphorus-based flame retardant elements, which, together with the diatomaceous earth flame retardant, construct a highly efficient flame retardant system. Furthermore, this modified network also enhances the interfacial bonding strength of the fibers, thereby imparting excellent flame retardant performance while avoiding the mechanical property degradation problem caused by conventional flame retardant treatments.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. Based on the present invention, some modifications or substitutions can be made, but these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of protection claimed by the present invention.
Claims
1. A flame-retardant high-strength fiberboard, characterized in that, By weight, it includes the following components: 90-100 parts modified wood fiber, 15-20 parts flame retardant, and 7-16 parts adhesive; The preparation process of the modified wood fiber is as follows: (1) Add wood fibers to anhydrous ethanol, then add isopropoxy titanium and trimethyloctadecyl ammonium chloride and heat to react. After the reaction is completed, filter, wash and dry to obtain pretreated wood fibers. (2) The pretreated wood fibers were added to deionized water, and then dimethyl aminomethylphosphonate, trimethoxy(3,3,3-trifluoropropyl)silane and aluminum chloride were added to react. After the reaction was completed, the mixture was centrifuged and dried to obtain the modified wood fibers. The preparation process of the flame retardant is as follows: Diatomaceous earth is added to N,N-dimethylformamide, and then propyltriethoxysilane is added. The mixture is reacted at 50-60°C for 1-3 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain the flame retardant.
2. The flame-retardant high-strength fiberboard according to claim 1, characterized in that, The ratio of wood fiber, isopropoxy titanium, and trimethyloctadecyl ammonium chloride used in step (1) is 1g:(30-60)mL:(20-50)g.
3. The flame-retardant high-strength fiberboard according to claim 1, characterized in that, The heating reaction in step (1) is carried out at a temperature of 40-50℃ for 8-10 hours.
4. The flame-retardant high-strength fiberboard according to claim 1, characterized in that, In step (2), the mass ratio of the pretreated wood fiber, dimethyl aminomethylphosphonate, trimethoxy(3,3,3-trifluoropropyl)silane, and aluminum chloride is 1:(0.1-0.3):(2-5):(2-4); the reaction time is 2-5 h.
5. The flame-retardant high-strength fiberboard according to claim 1, characterized in that, The mass ratio of diatomaceous earth to propyltriethoxysilane is 1:(0.05-0.15).
6. The flame-retardant high-strength fiberboard according to claim 1, characterized in that, The adhesive is an isocyanate adhesive.
7. The flame-retardant high-strength fiberboard according to claim 6, characterized in that, The adhesive also contains paraffin wax, which accounts for 0.5-2% of the adhesive by mass.
8. A method for preparing a flame-retardant high-strength fiberboard according to any one of claims 1-7, characterized in that, Includes the following steps: Weigh each raw material according to the stated weight proportions, mix the modified wood fiber and flame retardant evenly, then add the adhesive, stir evenly, transfer to a mold, and obtain the flame-retardant high-strength fiberboard through casting, rolling, and cooling.
9. The method for preparing flame-retardant high-strength fiberboard according to claim 8, characterized in that, The temperature of the roller press is 160-180℃, and the pressure is 2-3MPa.
Citation Information
Patent Citations
Fiber plate and manufacturing method thereof
CN106426497A
Flame-retardant high-density fiberboard and preparation method thereof
CN117183050A